Introduction to the special issue "From bullets to ballots: the transformation of rebel groups into political parties". Issue 6 (18th September 2016) - Ishiyama, John
ABSTRACT: In this special issue of Democratization, seven articles are presented that address the question of the transformation of armed rebel groups into political parties and what implications this transformation has on the development of post-conflict peace and democratization. The articles cover a wide variety of geographic cases, and use both quantitative and qualitative methods of inquiry.